Approaching accessibility: Four opportunities to address the needs of disabled people in transportation planning in the United States. (February 2023) - Levine, Kaylyn; Karner, Alex
Abstract: In common transportation planning practice and research, disability is largely mistreated and oversimplified. This review essay identifies four shortcomings in U.S. transportation planning that perpetuate oversight, exclusion, and inadequate transportation systems for disabled people. Compliance-based agendas are used by public agencies to implement accessibility accommodations based on minimum requirements, failing to consider the everyday experiences of disabled people. Data gaps and access to opportunity assumptions reveal how transportation planning and analysis approaches are inadequate when considering the disability community. Lastly, the narrow focus on mobility disability in the transportation field ignores the diversity of human conditions. These existing challenges are defined in detail with examples of how disability justice ideas and inclusive public engagement practices can address each shortcoming. Meaningful public engagement with the disability community would improve how transportation planning, policy, and practice address the needs and lived experiences of this critical population group. Highlights: Disabled people face complex barriers to travel. We identify four shortcomings that affect how travel barriers are addressed. Meaningful public engagement integrates lived experiences into planning. A transportation justice approach improves accessibility.